Artificial nest usage patterns of the endangered Siberian flying squirrel (Pteromys volans) released in natural habitat. Issue 4 (2nd October 2021) - Kim, Ki Yoon; Lim, Sang Jin; Ji Hong, Min; Kim, Hye Ri; Kim, Eui Kyung; Park, Yung Chul
Abstract: Siberian flying squirrel ( Pteromys volans ) is an endangered nocturnal flying mammal inhabiting the conserved forests in the Korean Peninsula. This study investigated the artificial nest usage patterns of a released Siberian flying squirrel individual and other wild species inhabiting the area using trail cameras. Our observations indicated that the released Siberian flying squirrel preferred artificial nests with an entrance diameter of 4 cm rather than 6.5 cm installed in the study area. Additionally, the Siberian flying squirrel used at least four nests. During winter, Eurasian nuthatch bird species competed with the Siberian flying squirrel for the nests. Therefore, to reduce competition for nests, further research on the nest entrance size, nest depth, and insulation material preferred by the Siberian flying squirrels and Eurasian nuthatch birds is necessary. This study provides significant information on whether artificial nests installed in areas, where rescued Siberian flying squirrels are released, can be used as early nesting sites by the Siberian flying squirrels to facilitate their easy re-settlement in the natural habitats.